Genetically Associated Hypertrophic Cardiomyopathy Combined with Persistent Left Superior Vena Cava (International Journal of Scientific Research and Management (IJSRM), 2023)
Background: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiomyopathy. An implantable cardioverter defibrillator (ICD) is an efficient way of preventing sudden cardiac death in these patients. Aim: Diagnosis and treatment of genetically associated hypertrophic cardiomyopathy. Case Report: We present a 28-year patient with a history of tachycardia, dizziness, transient chest pains, and anamnestic information on episodes of short-term loss of consciousness and fatigue. She has a positive family history of HCM and her uncle died young from sudden cardiac death (SCD). The electrocardiogram showed hypertrophy, which was confirmed with echocardiography and MRI. Genetic testing confirms PRKAG2 gene mutation. Holter24-hour ECG monitoring showed domination of sinus bradycardia after which it was recommended implantation of ICD. On implantation, persistent left superior vena cava (PLSVC) was discovered and the implantation side was changed. A bipolar Implantable Cardioverter Defibrillator was implanted. Conclusion: When HCM is confirmed at a young age, genetically associated HCM should always be considered. Early recognition of hereditary hypertrophic cardiomyopathy can facilitate better disease management and follow-up even before symptoms appear. Keywords: hypertrophic cardiomyopathy, PRKAG2 gene mutation, PLSVC, SCD, ICD.